Multicriteria Decision Making Taxonomy of Cloud-Based Global Software Development Motivators - Muhammad Azeem Akbar; Hussain Alsalman; Arif Ali Khan; Sajjad Mahmood; Chandrashekhar Meshram; Abdu H. Gumaei; Muhammad Tanveer Riaz (IEEE Access, 2020)
The software organizations widely consider the cloud based global software development (CGSD) as it offer the quality projects with low cast. The adoption of CGSD is challenging due to the geographical distance between practitioners. This study aims to identify and analyses the motivators that could positively impact the implementation of CGSD paradigm. The systematic literature review approach was applied to identify the CGSD motivators reported in the literature, and were further validated with industry experts using questionnaire survey study. Moreover, the fuzzy-AHP approach was applied to prioritize the investigated motivators concerning their significance for the successful adoption of CGSD. The findings of the study provide the prioritization-based taxonomy of the investigated motivators that assists the software organizations to develop and revise their strategies for the successful implementation of CGSD.